In-House Cinema / Adriana Sally Ronny... [et al.] - Wang Kee, Azlizan; Ahmad, Dayang Afaezah; Eddy, Elden Olivia; M. Michael, Mary Grace; Ronny, Adriana Sally (2013)
In-House Cinema is a type of business which offers high quality of fresh and new movies to customers, with prompt, friendly service in a clean and comfortable environment. This type of business is still new in Malaysia entertainment business market. This is due to the type of service which offers a private moments and different from any other cinema in Malaysia, especially in Sabah. The name chosen for the business operation is In-House Cinema. The term 'In-House' stands for the moment we capture during watching movie in our mini theatre as we are at home. In addition to that, it also shows the private moment we enjoy when we were at home. Why we are dare to take risk in this kind of business? It is surely because we believe that every opportunities lay in what we cannot see right now, but can be predicted and will be seen in the future, in the next one or two years ahead. One of the most important aspects that drive us to venture in this kind of business is because we realize the demand of the customer that need something new and will attract them especially among youths. For this reason, the business will be located at Wawasan Plaza Shopping Complex due to the development of economic in that particular area. There are several reasons why we choose Wawasan Plaza in our business operation. Of course, if we are seriously involved in this business field, we will find the best and profitable area to set our business field, by every partner, we can achieve our stated objectives, vision and mission.